Mechanical alloying and electrochemical hydrogen storage of Mg-based systems - Kalisvaart, W.P.; Notten, P.H.L. (Journal of materials research, 2008)
Results on mechanical alloying of binary and ternary Mg–Ti-based mixtures are reported. Using fine-powdered reactants and a process-control-agent, a mixture of two face-centered cubic compounds is obtained. Using a coarse Mg precursor without addition of a milling agent results in a hexagonal-solid solution of Ti in Mg due to a lower oxygen content in the Mg starting material. Upon introduction of Ni or Al as a third element, the amount of dissolved Ti decreases to form a nanocrystalline secondary phase. The electrochemical charging capacity of the hexagonal compounds is far superior to that of the cubic ones, whereas the discharge capacity is significantly increased only upon addition of Ni. The secondary TiNi phase acts as a rapid diffusion path for hydrogen, greatly improving the rate capability of the alloys. The reversible hydrogen storage capacity reaches values of up to 3.2 wt% at room temperature for (Mg0.75Ti0.25)0.90Ni0.10.